Diagnostic Possibilities of Ultrasound in Polycystosis of the Kidney - Xojirahmatov Davron (Genius Journals, 2023)
The article presents the results of examination of 4 patients suffering from polycystic kidney disease. It is noted that ultrasound methods are the most informative in the diagnosis of this pathology. The clinical course of polycystic disease was characterized by few symptoms . Despite the severity of morphological changes, kidney function suffered slightly. The possibility of dynamic changes in the size and content of cysts throughout life is assumed , as well as the presence of a congenital connective tissue defect in familial polycystic kidney disease.
Keywords: Ultrasound; diagnostics; polycystic kidney disease